Human Rights and Constitutionality Issues of Blasphemy Law in Indonesia - Ismail Hasani; Halili Halili (The Constitutional Court of the Republic of Indonesia, 2022)
This article analyzes human rights and constitutionality issues in the Indonesian Blasphemy Law. It contributes urgently to constitutional studies since constitutionalism requires respect for human rights and democracy obliges to uphold the supremacy of the constitution. This article was written as the results of research through the desk-study using descriptive-qualitative approach. Data were collected through document study and Internal Focus Group Discussion. Indonesia's blasphemy laws inherently violate human rights and are prone to politicization which places religious minorities in vulnerability, while the main legal provisions that criminalize blasphemy have been tested for their constitutionality dimensions by the Constitutional Court. However, the constitutionality issue remains, partly because the Constitutional Court affirmed a religious constitution whereas the Republic of Indonesia is a Pancasila based state. In addition, the Constitutional Court ignores human rights, particularly the right to freedom of religion/belief as guaranteed by the constitution.